Reciprocal Cosmopolitanism. - Drałus, Dorota (Problems / Problemos, 2020)
In the paper I analyse Daniele Archibugi's conception of the new cosmopolitanism, aimed at formulation of a theory of cosmopolitan democracy capable of facing contemporary global problems that go beyond the competences of nation-states. My claim is that the advocates of the new cosmopolitanism have yet to come up with a theoretical minimum to which all parties of the cosmopolitan debate would subscribe. I argue that the main obstacle in formulation of a viable cosmopolitanism are attempts at imposition of the universalist uniformity inscribed in the traditional cosmopolitanism or, at best, a straightforward acceptance of cultural differences. In opposition to this, I outline the idea of reciprocal cosmopolitanism which, I believe, should proceed from the acknowledgement of human diversity, thus becoming a more inclusive project than its existing alternatives.